2019
DOI: 10.1155/2019/5952836
|View full text |Cite
|
Sign up to set email alerts
|

TP53Mutations Promote Immunogenic Activity in Breast Cancer

Abstract: Background. Although immunotherapy has recently achieved clinical successes in a variety of cancers, thus far there is no immunotherapeutic strategy for breast cancer (BC). Thus, it is important to discover biomarkers for identifying BC patients responsive to immunotherapy. TP53 mutations were often associated with worse clinical outcomes in BC whose triple-negative subtype has a high TP53 mutation rate (approximately 80%). To explore a potentially promising therapeutic option for the TP53-mutated BC subtype, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 67 publications
11
33
0
Order By: Relevance
“…Besides, we tested whether the infiltration of immune cells is associated distinct mutations, and the results indicated that TP53 showed relatively obvious difference between the mutant and the wild type. These differences may illustrate that TP53 mutation may affect the immune microenvironment of breast cancer to a certain extent (the specific mechanism is not clear here), this is consistent with the conclusion of a recent study (Liu Z et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Besides, we tested whether the infiltration of immune cells is associated distinct mutations, and the results indicated that TP53 showed relatively obvious difference between the mutant and the wild type. These differences may illustrate that TP53 mutation may affect the immune microenvironment of breast cancer to a certain extent (the specific mechanism is not clear here), this is consistent with the conclusion of a recent study (Liu Z et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…TP53 missense mutations are strongly associated with the strong immuno positivity of p53 protein in breast (pvalue = 0.001417) and breast and colorectal cancer combined (p-value = 8.104e-06). Several previous studies which observed an association between TP53 mutations and higher expression of p53 protein in various types of cancer [33,34] also support our findings. A larger study done on 7878 variants representing 60 distinct tumour sites from the IARC TP53 Database concludes that missense mutations are IHC positive while nonsense mutations, frameshift mutations and deletions were immunonegative [35].…”
Section: Immunohistochemical Analysissupporting
confidence: 92%
“…Finally, breast cancer is a systemic disease and the involvement of WNT signaling should be considered from this perspective as well. Both in mice and humans, loss of TP53 has recently been associated with the induction of WNT protein production, which may in turn stimulate the immune system to promote metastasis (Kim et al, 2019;Liu et al, 2019;Wellenstein et al, 2019). Likewise, cytokine signaling from the local bone microenvironment may promote metastatic colonization by initiating an autocrine WNT signaling loop in human breast cancer stem cells (Eyre et al, 2019).…”
Section: Discussionmentioning
confidence: 99%